The Development of Resistance and Susceptibility of Aedes Aegypti Larvae and Adult Mosquitoes against Selection Pressure to Malathion, Permethrin and Temephos Insecticides and its Cross-Resistance Relationship against Propoxur - S, Subramaniam; Mohd Aris, Edah; Ahmad, Nazni Wasi; H.L, Lee; Hadi, Azahari Abdul (Malaysian Journal of Science, 2006)
In a response to mosquito-borne disease outbreak from time to time, the susceptibility of a medically important mosquito, Aedes aegypti was assessed to determine resistance development against chemical insecticides malathion, permethrin and temephos. World Health Organization (WHO) standard procedures were used namely, larval bioassay to determine the susceptibility of lethal concentration (LC) and adult bioassay to determine the lethal time (LT) in malathion, permethrin and temephos of selected resistant strains. These mosquito strains were bred in the Insectarium, Division of Medical Entomology, Institute for Medical Research (IMR), Malaysia. Colonies of these mosquito strains were established from the larvae by subjecting to selection pressure which yield 50% - 70% mortality level to the subsequent 10 generations. The. rate of resistance development and resistance ratio (RR) was calculated by LC50 and LT50 values for larval bioassay and adult bioassay respectively. The lab bred Aedes aegypti was used as a susceptible strain for comparison purpose. The adult bioassay test was carried out by using diagnostic dosages of malathion 5.0%, permethrin 0.75% and with propoxur 0.1 %. All bioassay results were subjected to probit analysis. The results exhibited the following insecticides shown degree of potency or effectiveness to larvae of Aedes aegypti when comparison made on its resistance ratio (RR) in ascending order permethrin > malathion> temephos. It was suggested that temephos is a promising chemical larvicidal agent for the control of Aedes aegypti larvae. In contrast, malathion and permethrin were the effective adulticide agent for the control of adult Aedes aegypti. There was some degree of a cross-resistance relationship against propoxur in these three strain.